Impact of chemical elements released by the volcanic eruption of La Palma (Canary Islands, Spain) on banana agriculture and European consumers. (April 2022) - Rodríguez-Hernández, Ángel; Díaz-Díaz, Ricardo; Zumbado, Manuel; Bernal-Suárez, María del Mar; Acosta-Dacal, Andrea; Macías-Montes, Ana; Travieso-Aja, María del Mar; Rial-Berriel, Cristian; Henríquez Hernández, Luis Alberto; Boada, Luis D.; Luzardo, Octavio P.
Abstract: The recent volcanic eruption on the island of La Palma has aroused the concern of banana producers and consumers, given that in its area of influence there are thousands of hectares of banana plantations with an annual production of about 100 million kilos for export. Since volcanoes are one of the main natural sources of heavy metal contamination, we sampled bananas from the affected area and determined the concentrations of 50 elements (Ag, Al, As, Au, Ba, Be, Bi, Cd, Ce, Co, Cr, Cu, Cu, Dy, Er, Eu, Fe, Ga, Gd, Hg, Ho, In, La, Lu, Mn, Mo, Nb, Nd, Ni, Os, Pb, Pd, Pm, Pr, Pt, Sb, Sc, Se, Sm, Sn, Sr, Ta, Tb, Th, Ti, Tl, Tm, U, Y, Yb and Zn). The levels of 36 elements were elevated but the washing implemented after the eruption can remove a good part. After the washout, bananas have elevated levels of Fe, Al, Ti, V, Ba, Pb, most of the rare earth elements, Mo, and Co. In all cases, except Mo, the elevation is much higher in the peel than in the flesh. In the case of Mo, the elevation in banana flesh would translate into a higher nutritional intake of this trace element, which could represent up to 35% of the daily nutritional requirements. Exposure to toxic or potentially toxic elements, does not represent a health risk, since would not exceed 5% of the tolerable daily intake, even in the worst-case scenario. Graphical abstract: Image 1 Highlights: Volcano bananas contain more molybdenum, capable of providing 35% of the RDI. Washing the bunch can remove most of the toxic elements deposited on the bananas. Concentrations of Mo, Co, Pb, Fe, Al, Ti, V, and REE were increased in the flesh of volcano bananas. The banana skin accumulates much higher concentrations of toxic elements than the flesh. In the worst-case scenario, they would provide less than 5% of the tolerable daily intakes of toxic elements.